PROFIL TERAPI OBAT PADA PASIEN ISPA DI PUSKESMAS KOTA TENGAH TAHUN 2019 - Sutriyati Tuloli, Teti; Rasdiana, Nur; Bakululu, Lesmiyati (Indonesian Journal of Pharmaceutical Education, 2022)
Acute respiratory infections (ARI) is an infectioan that commonly occurs in human of any age however, children and infants are the most vulnerable and most exposed to ARI. The study aims to identify the utilization of drug therapy in patients with ARI, specifically those infants and children patients at Puskesmas Kota Tengah in 2019. it employs a descriptive research design where the obtained data are secondary data that are collected retrospectively besides, the data used in this study are medical prescription documents, including the patientâ€™s name, age, type of drug used, and drug use patternThe finding discloses that drug therapy administered to 116 infants and children patients who suffer from ARI at Puskesmas Kota Tengah in 2019 reveals that the most widely used therapy is the expectorant group(Gliceryl Guaicolate) as many as 61 (62,2%), Antihistamine group (Chlorpheniramine maleate) with a frequency of 75 times (64,1%), Vitamin B Complex with a frequency of 69 times (55,2%), Antibiotik group (Amoxicillin) with a frequency 47 times (41%), Analgesic and Antipyretic group (Paracetamol) is the most widely prescribed with a prescription frequency of 65 times (55,7%). In addition, the parameter of right drug obtains frequency of 22 times with 94 times with the percentage of (81,0%) and incorrect drug obtains a frequncy of 22 times with a percentage of (19,0%), the parameter of right dose for 83 times with a percentage of (71,6%), and incorrect dose for 33 times with a percentage of (28,4%). At the same time, the right drug use pattern parameter involves the right dose, and the right drug obtains a frequency ofÂ  94 times with a percentage 0f 8 (81,0%) while the incorrect drug use pattern obtains a frequency 0f 22 times with a percentage 0f (19,0%)